A RARE METASTATIC REGION OF CERVICAL CANCER; THE BRAIN: A CASE REPORT - Alabi Adewumi O; Habeebu Muhammad Y; Alabi Adegboyega S; Sowunmi Anthonia C (Ntec Specialist, 2020)
Background: Cervical cancer metastasizes commonly to the bone, lungs, liver and the supraclavicular lymph nodes. Rare sites of metastasis the brain, breast, paraspinal muscles, duodenum and heart have been reported. Case report: A 53-year-old postmenopausal woman presented to our facility with a one-month history of vaginal bleeding. She was found to have an exophytic cervical mass on pelvic examination. She was managed as a case of stage IIIB cervical cancer. Histology revealed Squamous Cell Carcinoma type. She had radiotherapy and was symptoms free. She represented 3 months later with visual disturbance, headache and vomiting. She was found to have metastatic lesion to her brain. She survived for 3 months and 3weeks after first treatment. Conclusion: The prognosis of cervical cancer patients with brain metastases is frequently poor with median survival of only a few months such as in this case who survived 3 months and 3 weeks after first treatment. Only few reports have incidences of long-term, disease-free survival in these patients